Does Capacity Utilization Rate Affect Imports of Raw Materials in Nigeria? - OSIGWE, Augustine C.; Obi, Kenneth (International Journal of Economics and Financial Issues, 2015)
This study adopted a modified traditional import demand framework to examine the effects of capacity utilization rate on imports of raw materials in Nigeria. A number of striking results emerged from the analysis of data. 1 percent increase in capacity utilization rate causes import of raw materials to increase by 1.1 percent. 1 percent increase in the real exchange rate (depreciation of the Naira) reduces import of raw materials by 0.12 percent whereas 1 percent increase in domestic inflation results into a 0.72 percent decrease in the importation of raw materials. Expectedly, we found that a 1 percent increase in real gross domestic product triggers a 77 percent increase in imports of raw materials. In line with the traditional import function, we discovered that foreign exchange earnings positively and significantly determine imports of raw materials. On the basis of our findings, we recommend that the relevant stake holders should make genuine efforts towards boosting Nigeria’s capacity utilization rate. This recommendation stems from the fact that many of the local manufacturing firms depend heavily on imported raw materials. Keywords: Capacity Utilization Rate; Import; Raw Materials, GMM JEL Classifications: C13; C3; F1